Komunikasi Pelaku Usaha Mikro Terhadap Kesadaran Kepemilikan Sertifikasi Halal di Kecamatan Parung - Fadillah, Nurhadi; Abdul Qodir (Program Studi Komunikasi dan Penyiaran Islam, 2024)
This study aims to determine the level of awareness of micro business actors in Parung District regarding halal certification ownership. The research method used is a qualitative approach by conducting communication through observation and interviews with 23 micro business actors in food and beverages, as well as administrators of KUA and UMKM administrators in Parung District. From the results of the study, it was found that the factors that influence the awareness of business actors in having a halal certificate, namely the lack of knowledge regarding the rules for owning a Halal Certificate, the absence of curiosity about the purpose and importance of a Halal Certificate, business actors believe that their products are products that are guaranteed to be halal because they are not products that are prohibited by sharia, lack of compliance or legal compliance with the ownership of a Halal Certificate for a product. So that there are still many business actors who violate the provisions of the regulations governing the Halal Certificate in each of their products, the lack of supervision and even socialization by the management of UMKM in Parung District. From several factors obtained from the results of communication with the Resource Person, it can be concluded that the level of awareness of micro business actors in Parung District regarding the ownership of a halal certificate is still low.